2020 list of human papillomavirus assays suitable for primary cervical cancer screening. (August 2021) - Arbyn, Marc; Simon, Marie; Peeters, Eliana; Xu, Lan; Meijer, Chris J.L.M.; Berkhof, Johannes; Cuschieri, Kate; Bonde, Jesper; Ostrbenk Vanlencak, Anja; Zhao, Fang-Hui; Rezhake, Remila; Gultekin, Murat; et al.
Abstract: Background: Only clinically validated HPV assays can be accepted in cervical cancer screening. Objectives: To update the list of high-risk HPV assays that fulfil the 2009 international validation criteria (Meijer-2009). Data Sources: PubMed/Medline, Embase, Scopus, references from selected studies; published in January 2014 to August 2020. Study eligibility criteria: HPV test validation studies and primary screening studies, involving testing with an index HPV test and a comparator HPV test with reporting of disease outcome (occurrence of histologically confirmed cervical precancer; CIN2+). Participants: Women participating in cervical cancer screening. Interventions: Testing with an index and a comparator HPV test of clinician-collected cervical specimens and assessment of disease outcome (<CIN2, CIN2+). Comparator HPV assays were HC2, GP5+/6+ PCR-EIA, recommended in validation guidelines, or tests with consistent previous validations. Methods: Assessment of relative clinical accuracy (including non-inferiority statistics index vs comparator assay) and test reproducibility in individual studies; random effects meta-analyses of the relative clinical sensitivity and specificity of index vs comparator tests. Results: Seven hrHPV DNA tests consistently fulfilled all validation criteria in multiple studies using predefined test positivity cut-offs (Abbott RealTi m e High Risk HPV, Anyplex II HPV HR Detection, BD Onclarity HPV Assay, Cobas 4800 HPV Test, HPV-Risk Assay, PapilloCheck HPV-Screening Test and Xpert HPV). Another assay (Alinity m HR HPV Assay) was fully validated in one validation study. The newer Cobas 6800 HPV Test, was validated in two studies against Cobas 4800. Other tests partially fulfilled the international validation criteria (Cervista HPV HR Test, EUROArray HPV, Hybribio's 14 High-Risk HPV, LMNX Genotyping Kit GP HPV, MALDI-TOF, RIATOL qPCR and a number of other in-house developed assays) since the non-inferior accuracy was reached after a posteriori cut-off optimization, inconsistent accuracy findings in different studies, and/or insufficient reproducibility assessment. The APTIMA HPV Assay targeting E6/E7 mRNA of hrHPV was fully validated in one formal validation study and showed slightly lower pooled sensitivity but higher specificity than the standard comparator tests in seven screening studies. However, the current international validation criteria relate to DNA assays. The additional requirement for longitudinal performance data required for non-DNA based HPV assays was not assessed in this review. Conclusions: Eleven hrHPV DNA assays fulfil all requirements for use in cervical cancer screening using clinician-collected specimens.